What is the resulting equation when the expression for y in the second equation is substituted into the first equation?3x + y = 1
y = 6 - 4x

a. -x + 6 = 1
b. x + 6 = 1
c. 7x + 6 = 1

Answers

Answer 1
Answer:

Answer:

When expression for y in the second equation is substituted into the first equation than the resulting equation -x + 6 = 1 .

Option (a) is correct .

Step-by-step explanation:

As given the equations in the questions are

3x + y = 1

y = 6 - 4x

As expression for y in the second equation is substituted into the first equation .

i.e put y = 6 - 4x in 3x + y = 1  .

3x + 6 - 4x = 1  

Solving the above

-x + 6 = 1

Therefore the when expression for y in the second equation is substituted into the first equation than the resulting equation -x + 6 = 1 .

Option (a) is correct .

Answer 2
Answer: 3x + y = 1

3x + (6 - 4x) = 1

3x + 6 -4x = 1

3x - 4x + 6 = 1

-x + 6 = 1

Therefore (a)

Related Questions

What is the area of a triangle base 25 feet and height 8 feet
The corresponding sides of two similar triangles are (congruent or proportional).The corresponding angles of two similar triangles are (congruent or proportional)
What’s the area of parallelogram A shown?
Given: Circle O and Circle Q intersect at R and S;mRVS=60; mRUS=120 Prove: OR is tangent to circle Q QR is tangent to circle O
Sheri wants to know how the 1,090 students at her school feel about after-school programs She selects each of these samples randomly. Is each a representative sample of the population

Traditions Clothing Store is having a sale. Shirts that were regularly priced at $20 are on sale for $17. What is the percentage of decrease in the price of the shirts?

Answers

\begin{array}{ccc}\$20&-&100\%\n\n\$17&-&p\%\end{array}\n\n\ncross\ multiply\n\n20p=17\cdot100\ \ \ /:20\n\np=(1700)/(20)\n\np=85\ (\%)\n\n100\%-85\%=15\%\leftarrow Answer
original price of shirts  = $ 20
new price of shirts =  $17
decrease in price =  $20 - $17  = $ 3
% decrease =        3/20 x 100 =  15%

V^2+3v-5=0
Round to nearest hundredth

Answers

v² + 3v - 5 = 0
v = -(3) ± √((3)² - 4(1)(-5))
                    2(1)
v = -3 ± √(9 + 20)
                2
v = -3 ± √(29)
            2
v = -3 ± 5.38
            2
v = -1.5 ± 2.69
v = -1.5 + 2.69    or    v = -1.5 - 2.69
v = 1.19    or    v = -3.19

Find the midpoint of the segment with the following endpoints. (6, 4) and (9,9)

Answers

Answer:

15/2, 13/2.

Step-by-step explanation:

Here's a graph as well.

Answer in fraction form = (15/2, 13/2)

Answer in decimal form = (7.5, 6.5)

========================================================

Explanation:

To get the midpoint, we average the two endpoint values. We handle the x and y coordinates separately.

The x coordinates of each point are 6 and 9. They average to (6+9)/2 = 15/2 = 7.5; so you add up the x coordinates and divide by 2.

The y coordinates are handled the same way. Add them to get 4+9 = 13 and then divide by 2 to get 13/2 = 6.5

The midpoint is (15/2, 13/2) = (7.5, 6.5)

A swimming pool holds 900 cubic meters of water. If its length is 20 meters and its height is 3 meters, find its width

Answers

V=900m³

V=L*w*h

V=20*3*w
V=60*w

60*w=900

w=900/60
w=15m
Volume \ of \ a \ Cuboid: \n \n V=9000 m^3 \nthe \ length : \ l=20 \ m \n the \ height: \ h=3 m \n the \ width : \ w= ? \n \nV= l\cdot w \cdot h \n \n900 =20 \cdot w \cdot 3 \n \n900=60w \ \ / :60\n \n w=15 \ m \n\nAnswer : \ A \ swimming \ holds \ 15 \ meters\ the \ width .

What is the solution for the inequality |-5x+2|<7

Answers

i'm just gonna try my best.
it will be -5x+2=7
let's ignore the less than sign, so it will be -5x=7-2
   ; -5x=5
   ; x=-1
If the question asks you to graph it, you will graph -1 less than 7 or -17
i'm sorry that i cant find the less than sign
|-5x + 2| < 7
|-5x + 2| < ±7
|-5x + 2| < 7    or    |-5x + 2| < -7
  -5x + 2 < 7      or    -5x + 2 < -7
         - 2  - 2                    - 2   - 2
        -5x < 5       or         -5x < -9
         -5    -5                    -5    - 5
           x < -1        or        x < 1⁴/₅

How do I factor this?
X^2-12x+36

Answers

x^2-12x+36 =\n (x-6)^2
x^2-12x+36 \n =x^2-2*6x+6^2 \n\boxed{ =(x-6)^2}